Journey to Italy - Sade, marquis de, 1740-1814 (Lorenzo da Ponte Italian library., 2020)
"In the mid-1770s, the Marquis de Sade fled to Italy from France after being accused of mistreatment by multiple prostitutes and sentenced to death by sodomy and poisoning. This book is an English translation of his Voyage d'Italie, an unfinished and unpolished project that he wrote while travelling throughout Florence, Rome and Naples for about a year. Blending travel writing and philosophy, the work includes descriptions and analyses of the Italian landscape, architecture, and art, as well as examinations of the social more and culture practices of the Italian people. In his substantial introduction and extensive annotations, James A. Steintrager demonstrates how Sade's travels in and writings about Italy would have a major impact on his later, much more famous and controversial works, including The 120 Days of Sodom (1785) and Justine (1791)."--